2015
DOI: 10.1515/intox-2015-0028
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and antigenotoxicity study of aqueous and hydro-methanol extracts of Spondias mombin L., Nymphaea lotus L. and Luffa cylindrical L. using animal bioassays

Abstract: Spondias mombin (Linn), Nymphaea lotus (Linn) and Luffa cylindrica (Linn) (syn Luffa aegyptiaca Mill) are plants traditionally used as food ingredients and in the management of diseases, including cancer, in Nigeria. Despite the therapeutic potentials attributed to these plants, reports on their genotoxicity are scanty. In this study, the genotoxicity of the aqueous and hydro-methanol extract of these plants was evaluated using mouse bone marrow micronucleus and sperm morphology assays. Antigenotoxicity was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Therefore, the presence of these toxic elements (but not N. lotus itself) could explain the toxic effects of the hydro-ethanolic and hydro-methanolic extracts of N. lotus reported in the literature. These toxic effects were characterised by an induction of a chromosomal aberration in rat lymphocytes, an increase of aberrant sperm cells and somatic genotoxicity [ 49 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of these toxic elements (but not N. lotus itself) could explain the toxic effects of the hydro-ethanolic and hydro-methanolic extracts of N. lotus reported in the literature. These toxic effects were characterised by an induction of a chromosomal aberration in rat lymphocytes, an increase of aberrant sperm cells and somatic genotoxicity [ 49 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo MN assay is widely utilised to evaluate the ability of test agents to induce chromosomal damage and/or mitotic disturbances (Hwang et al, 2013;Oyeyemi et al, 2015). The result of the MN assay showed that TDF, efavirenz and their combination are clastogenic and/or aneugenic at the tested doses.…”
Section: Discussionmentioning
confidence: 99%
“…44 Aqueous S. mombin extracts exhibited the potential to induce genetic damage in both somatic and germ cell lines. In addition, they counteracted the effects of known mutagens or carcinogens, 45 which may be responsible for the difference in their bioactivities. Therefore, Spondias mombin can be a good source of natural pesticides and antitumor agents.…”
Section: Cytotoxicitymentioning
confidence: 99%